Pengaruh Komunikasi Dan Motivasi Kader PPKBD Dan Sub PPKBD Dalam Peningkatan Jumlah Keluarga Berencana Di Kecamatan Tanjung Harapan Kota Solok - Mega Husnayanti; Afniyeni Afniyeni; Nurhayati Nurhayati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research was conducted on PPKBD Cadres and Sub PPKBD Sub-districts of Tanjung Harapan, Solok City. The purpose of this study was to determine how much influence the communication and motivation of PPKBD and Sub PPKBD Cadres had in increasing the number of family planning. In this study, the population was PPKBD Cadre and Sub PPKBD, which amounted to 75 people. With this type of quantitative research and sampling technique using the total sampling method. The data collection technique used is by using a questionnaire/questionnaire. Based on multiple linear regression analysis of the variables of Communication and Motivation of PPKBD Cadres and Sub PPKBD in Increasing the Number of Family Planning Y = 19.221 + 0.274X1 + 0.299X2 + e. From the t-test that was carried out, it was found that the X1 variable of PPKBD Cadre Communication and Sub PPKBD had a significant effect on increasing the number of family planning with t count greater than t table 2.880 > 1.993. Then Ha is accepted and H0 is rejected. Variable X2 Motivation of PPKBD Cadres and Sub PPKBD has a significant effect on increasing the number of family planning, the value is known to be tcount > ttable, which is 3,157 > 1,993. Then Ha is accepted and H0 is rejected. From the f test, it was found that the Communication and Motivation of PPKBD Cadres and Sub PPKBD Cadres could simultaneously increase the number of Family Planning with fcount 10,647 > ftable 3,124. Then Ha is accepted and H0 is rejected. From the Determination Test the R Square value is 0.228. This means that the effect of the independent variable on the dependent variable is 22.8%, while the remaining 77.2% is influenced by other variables..